In vitro activity of ciprofloxacin, ofloxacin and levofloxacin against Mycobacterium tuberculosis - Akcali, Sinem (Ann Saudi Med, 2005)
BACKGROUND: The increasing incidence of drug-resistant Mycobacterium tuberculosis necessitates therapeutic alternatives. The fluoroquinolones fulfill most of the criteria for an ideal class of antimycobacterial drugs. The aim of the present study was to determine to in vitro activities of ciprofloxacin, ofloxacin, and levofloxacin against M. tuberculosis strains. METHODS: Susceptibility to four antituberculous drugs used in first-line treatment of tuberculosis was tested in 100 strains isolated from clinical samples. Nineteen strains (19%) were resistant to at least one of the four antituberculous drugs and 13 were multidrug resistant. The in vitro antimycobacterial activity of ciprofloxacin, ofloxacin, and levofloxacin was then determined against 100 M. tuberculosis strains using standard agar proportion dilution method. RESULTS: Ciprofloxacin, ofloxacin, and levofloxacin were active against all tested strains of M. tuberculosis in vitro. CONCLUSIONS: Ciprofloxacin, ofloxacin, and levofloxacin have relatively potent in vitro activity against M. tuberculosis. Further in vivo studies are needed to determine the role of these compounds in the treatment of tuberculosis, but use should be limited to special circumstances rather than first-line treatment.